Adherence to the Mediterranean diet is inversely associated with visceral abdominal tissue in Caucasian subjects. Issue 6 (December 2015) - Bertoli, Simona; Leone, Alessandro; Vignati, Laila; Bedogni, Giorgio; Martínez-González, Miguel Ángel; Bes-Rastrollo, Maira; Spadafranca, Angela; Vanzulli, Angelo; Battezzati, Alberto
Summary: Background: & aim: Adherence to the Mediterranean dietary pattern (MDP) is inversely related with abdominal adiposity as detected by waist circumference but the specific association to subcutaneous and visceral abdominal tissue has not been investigated. To this purpose we evaluated the association between MDP, visceral (VAT) and subcutaneous (SAT) abdominal tissue in a large sample of Italian adults. Methods: A cross-sectional study was carried out on 4388 consecutive adults (73.2% women) followed as outpatients at Nutritional Research Centre in Milan, ICANS. VAT and SAT were measured by ultrasonography. MDP was evaluated using a Mediterranean dietary score (MEDscore) obtained from a validated 14-item questionnaire. Results: At multiple linear regression adjusted for sex, age, smoking and physical activity, a 1-unit increase in MEDscore was associated with a −0.118 kg/m 2 decrease in BMI (p < 0.01), a −0.292 cm decrease in waist circumference (p < 0.01), a −0.002 cm:cm decrease in waist to height ratio (p < 0.001), a −1.125 mm decrease in the sum of 4 skinfolds (p < 0.001), and with a −0.045 cm decrease in VAT (p < 0.05). MEDscore was, however, not associated with SAT. Finally, the adherence to the MDP was a protective factor for obesity (OR = 0.717, 95%CI: 0.555–0.922) and VAT excess (OR = 0.717, 95%CI: 0.530–0.971). Conclusion: Our study confirms the inverse association between MDP, BMI and waist circumference and adds that the association with abdominal obesity as detected by waist circumference is due to an association with VAT and not with SAT.